2010
DOI: 10.1590/s0100-69162010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of five sugar cane planters

Abstract: ABSTRACT:Brazil is the world biggest producer of sugar cane with an area of 7x10 6 hectares. Mainly the system used for planting is the semi-mechanized one, which consists in opening the furrows with a machine, manually allocating the fractioned stalks and then covering the furrows done by the machines. The great amount of human labor used in the semi-mechanized system is becoming harder to find and also more expensive, indicating the need of a fully mechanized operation. Currently in Brazil these agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The data distribution interquartile range, although within the control limits, exhibits deficient metering mechanisms, which is the greatest challenge to sugarcane planters given the billet size variability (Ripoli and Ripoli, 2010). The authors evaluated five sugarcane planters and observed the same limitation in all machines.…”
Section: Resultsmentioning
confidence: 98%
“…The data distribution interquartile range, although within the control limits, exhibits deficient metering mechanisms, which is the greatest challenge to sugarcane planters given the billet size variability (Ripoli and Ripoli, 2010). The authors evaluated five sugarcane planters and observed the same limitation in all machines.…”
Section: Resultsmentioning
confidence: 98%
“…The hourly fuel consumption in the operation of sugarcane mechanized planting, using a Civemasa billets cutter planter, model PCSA 2/2, being pulled by a tractor of 161 kW and operating at 2.200 rpm, with speed of approximately 5.0 km h -1 , was 40.24 L h -1 according to M. L. C. Rípoli and T. C. C. Rípoli (2010), higher than that obtained in this study, due to the fact the tractor used for this operation have less engine power (136 kW). It was also observed that, if it is compared the two mechanized plantations, and if it is used a tractor with 136 kW engine for this operation, as in this study, it can pull the planter of chopped sugarcane with an hourly fuel consumption of approximately 35% lower than compared to a tractor with 161 kW of engine power.…”
Section: Performance Of Mechanized Set -Tractor-plantermentioning
confidence: 99%
“…Another factor that may be taken into account is that, for day and night operation shifts, there was concentration of points slightly below the average, as can be evidenced by the distribution tails of values in the box plot graphics, and that can be proven by the coefficients of skewness, although at night, the mean was trivially larger than the median. M. L. C. Rípoli and T. C. C. Rípoli (2007) found values of effective consumption of fuel for mechanized planting of sugarcane very close to the present work, using tractors with power of 136 kW, and this being essential for the performance evaluation of operation of mechanized planting of sugarcane, because it can reflect the improvement in production costs through a proper management (Yadav et al, 2003). Kumar and Singh (2012) studied a model of sugarcane planter, khalsa brand, P-603 model, using a tractor with less power and a planter of less mass, operating at a working speed of 1.8 to 2.5 km h -1 , and they reported that the effective fuel consumption was 22 L ha -1 , a situation close to that found in this study, despite the conditions of the tractors and the machines be different.…”
Section: Performance Of Mechanized Set -Tractor-plantermentioning
confidence: 99%
“…Labour costs and shortages have increased due to social and environmental policies, indicating the necessity of fully mechanising this operation (Rípoli and Rípoli, 2010;Barros and Milan, 2010). Accordingly, most sugarcane planting operations are labour intensive; therefore, there is an urgent need to introduce the use of machines termed planters, which complete all crop management practices within a single operation (furrowing, fertilisation, distribution of buds, application of agricultural pesticides, and furrow closing and compaction) to increase the sustainability and overall productivity of the sugarcane plantation (Voltarelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%